BINGKAI BERITA DUGAAN BISNIS POLYMERACE CHAIN REACTION (PCR) LUHUT BINSAR PANDJAITAN PADA MEDIA ONLINE TEMPO.CO (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
Mass media has an important role in the process of forming public opinion. Good or bad opinions are formed depending on how the media packages the news they convey. In this case, the media can provide calm and is also able to create chaos. The media can raise someone's name, and can even kill someone's character. This type of research is qualitative descriptive research with a framing analysis data processing method which aims to find out how the media Tempo.co edition 01-15 November 2021 constructs news about the alleged Polymerase Chain Reaction (PCR) business involving the Coordinating Minister for Maritime Affairs and Investment (Menko Marves) Luhut Binsar Pandjaitan. The analysis technique used is Robert N. Entman's framing analysis. In this research, it was concluded that Pertama Tempo. co chose the PCR business issue and highlighted Luhut's involvement in the PCR business issue. In its news, tempo.co wrote news headlines that always mentioned Luhut's name. The news frame used by Tempo.co places Luhut Binsar Pandjaitan as an actor in the PCR business. Second, there was an attempt to assassinate Luhut Binsar Pandjaitan's character. Tempo.co appears to be trying to attack Luhut's involvement in the PCR business and form the label "PCR business" on Luhut. Third, Tempo is trying to criticize the government in the hope that its news can influence regulation-making and decision-making regarding the Polymerase Chain Reaction (PCR) test.